Banalization of Cultural Journalism. Media Show and Cultural Content in Peruvian press - Atarama-Rojas, Tomás (2017)
Cultural Journalism is one of the most important fields of information in social life. Since its inception, it has been linked to the written press and to the world of sciences, arts and letters, and today, it has become a wide space of varied topics, which includes not only the most relevant events of the cultural world, but also those of entertainment and media show. Given this scenario, this research seeks to demonstrate, through a content analysis of three of the most important national newspapers in the peruvian written press (El Comercio, La República, Perú21) that cultural contents have been replaced by questions of “farandula”, gossip and mediatic facts, contributing to an increasingly negative meaning of entertainment journalism and the trivialization of true Cultural Journalism.